EXPERIMENTAL ANALYSIS OF A 2.4 GHZ ANTENNA FOR TYRE PRESSURE MONITORING SYSTEM (Journal of Engineering Studies and Research, 2023)
Antennas used for tyre pressure monitoring systems are usually enclosed by the tyre. On its own, the antenna may have excellent properties. However, the wheel and tyre may have an impact on the performance of the antenna. This paper investigated the performance of a simple 2.4 GHz whip antenna for a tyre pressure monitoring system. The antenna was modelled using HFSS, while the wheel and tyre were modelled using SolidWorks. The wheel and tyre can have an impact on the antenna performance. The reflection coefficients, VSWR, gain and radiation pattern were determined through simulations, using HFSS. The antenna operation was checked at different positions and configurations to the wheel to determine its’ optimum position for effective signal radiation. The four different configurations were: antenna grounded to the middle of the rim, antenna ungrounded to the wheel’s edge, antenna grounded to the wheel’s edge, and antenna grounded to the wheel’s edge enclosed by the tyre. The result shows that electrically grounding the antenna to the wheel by the edge improves its performance. Also, the tyre did not negatively impact the far-field gain of the antenna.
Keywords: 2.4 GHz antenna, VSWR, reflection coefficient, antenna gain, TPMS